Exploring Synergistic Inhibition of Inflammatory and Antioxidant Potential: Integrated In Silico and In Vitro Analyses of Garcinia mangostana, Curcuma comosa, and Acanthus ebracteatus - Komgrit Eawsakul; Kingkan Bunluepuech (Advances in Pharmacological and Pharmaceutical Sciences)
Compared with the use of a single herb alone, herb combinations can significantly increase their effectiveness in treating various diseases. The objective of this research was to determine the appropriate proportions of Garcinia mangostana (GM), Curcuma comosa (CC), and Acanthus ebracteatus (AE) to enhance their antioxidant and anti-inflammatory properties. The study employed computer modeling (in silico) and laboratory testing (in vitro). The optimal levels of phenolic and flavonoid compounds were achieved with a ratio of 15 parts GM, 5 parts CC, and 10 parts AE. In contrast, the 10 : 15 : 5 ratio resulted in the highest antioxidant activity, reducing DPPH radicals by 80.33% and ABTS radicals by 92.20%. The ratio had a synergistic effect and was within the safe range, ranging from 82.97 to 147.04 µg/mL. The ratio of 5 : 10 : 15 had the greatest anti-inflammatory effects, with an exceptional activity level of 98.86%. It effectively suppressed 23 genes or proteins, including the prominent NFE2L2 gene, and had a synergistic effect. This combination effectively inhibits inflammation (IC50: 12.05 µg/mL) and is safe for macrophages at concentrations up to 50 µg/mL. These findings emphasize the potential of these herbal mixtures for antioxidant and anti-inflammatory applications.